Evaluation of thermal injury to liver, pancreas and kidney during irreversible electroporation in an in vivo experimental model. Issue 9 (24th June 2014) - Dunki-Jacobs, E M; Philips, P; Martin II, R C G
Abstract: Background: Irreversible electroporation (IRE) is a new technique for tumour cell ablation that is reported to involve non-thermal-based energy using high voltage at short microsecond pulse lengths. In vivo assessment of the thermal energy generated during IRE has not been performed. Thermal injury can be predicted using a critical temperature model. The aim of this study was to assess the potential for thermal injury during IRE in an in vivo porcine model. Methods: In vivo continuous temperature assessments of 86 different IRE procedures were performed on porcine liver, pancreas, kidney and retroperitoneal tissue. Tissue temperature was measured continuously throughout IRE by means of two thermocouples placed at set distances (0·5 cm or less, and 1 cm) from the IRE probes within the treatment field. Thermal injury was defined as a tissue temperature of 54°C lasting at least 10 s. Tissue type, pulse length, probe exposure length, number of probes and retreatment were evaluated for associations with thermal injury. In addition, IRE ablation was performed with metal clips or metal stents within the ablation field to determine their effect on thermal injury. Results: An increase in tissue temperature above the animals' baseline temperature (median 36·0°C) was generated during IRE in all tissues studied, with the greatest increase found at the thermocouple placed within 0·5 cm in all instances. On univariable and multivariable analysis, ablation in kidney tissue (maximum temperature 62·8°C), ablation with a pulse length setting of 100 µs (maximum 54·7°C), probe exposure of at least 3·0 cm (maximum 52·0°C) and ablation with metal within the ablation field (maximum 65·3°C) were all associated with a significant risk of thermal injury. Conclusion: IRE can generate thermal energy, and even thermal injury, based on tissue type, probe exposure lengths, pulse lengths and proximity to metal. Awareness of probe placement regarding proximity to critical structures as well as probe exposure length and pulse length are necessary to ensure safety and prevent thermal injury. A probe exposure of 2·5 cm or less for liver IRE, and 1·5 cm or less for pancreas, with maximum pulse length of 90 µs will result in safe and non-thermal energy delivery with spacing of 1·5–2·3 cm between probe pairs. Surgical relevance In this experimental investigation, irreversible electroporation (IRE) is studied in a porcine model to establish set device and probe guidelines, so that any type of thermal damage can be avoided. This IRE device is currently in use in the treatment of locally advanced soft tissue tumours, and the issue of potential thermal damage is therefore of clinical interest. This is further underlined by the fact that there is an underestimation among some IRE end-users that IRE energy delivery is non-thermal regardless of the circumstances. It is shown here that IRE can generate thermal energy, and even thermal injury, based on tissue type, probe exposure lengths, pulse lengths and proximity to metal (clips and stents). Abstract : Irreversible electroporation can cause thermal damage